2021
DOI: 10.3390/su13147757
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Climate-Smart Agriculture Technologies to Food Self-Sufficiency of Smallholder Households in Mali

Abstract: Climate change has resulted in food insecurity for the majority of farming communities in the Sudano-Sahelian zone of Mali. In this paper, we present a methodology for scaling climate-smart agriculture (CSA) technologies such as Contour Bunding (CB), Microdosing (MD), Intercropping (IC), Zaï pits, and Adapted crop Variety (AV) treatments, and evaluated their contribution to smallholder households’ food self-sufficiency. We used the participatory technology selection method and on-farm demonstration in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…It should result in livelihood improvement through the development of agroforestry in the context of its climate-smart context to face environmental challenges [58]. The application of the above-mentioned context in technologies led to increased food production, especially in places where food insecurity is one of the main categories of disasters [59]. Nonetheless, climate change has an impact on Sahelian agriculture.…”
Section: Environmental Landscape Of G5 Sahelmentioning
confidence: 99%
“…It should result in livelihood improvement through the development of agroforestry in the context of its climate-smart context to face environmental challenges [58]. The application of the above-mentioned context in technologies led to increased food production, especially in places where food insecurity is one of the main categories of disasters [59]. Nonetheless, climate change has an impact on Sahelian agriculture.…”
Section: Environmental Landscape Of G5 Sahelmentioning
confidence: 99%
“…The sustainability of indigenous practices, including chololo pits, in crop production has remained a challenge in many parts of arid and semi-arid parts of the world (Mswima & Kaswamila, 2022;Mswima, 2020;Qin et al, 2022;Traore et al, 2021).The moisture limitations due to climate change have brought challenges such as environmental stress, deterioration of vegetation cover, losses in agricultural production, loss of arable land, soil erosion, and increased stress on the economy, amongst others (Nyakudya et al, 2014). Studies have shown that these impacts have reduced overall crop productivity by 30% in Asia, and 13% in Africa (Saylor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These technologies improve soil fertility and curtain drought effects. Using the zaï technique in the Sahelian countries conserves water, enhances soil nutrients and increases yields(Traore et al, 2021); it requires many resources, such as time and labour.However, half-moon, stone buds, mulching and Farmer Managed Natural Regeneration (FMNR) are least practised due to the nature of the farmlands. The topography of the land, water retention ability, soil structure, and Tassa (zaï pits), Farmer Managed Natural Regeneration (FMNR) and stone buds are preferred CSAT adopted by farmers in rural Niger.…”
mentioning
confidence: 99%